Urban sustainability assessment of development and urbanization tools Case study of land occupancy plan No. 08 in the city of Ain Khadra, Algeria - Arab, Walid; Mohamed, Mili; Saoudi, Hadjer (Technium Social Sciences Journal, 2022)
Urban sustainability has become a prominent element in the discussion of urban policies and the expression of sustainability policy in planning and urban development decisions, as society has become more aware of the consequences of reckless urban development decisions, as well as the need to protect the environment from deterioration due to economic growth and irrational consumption of resources, as urban sustainability is seen as the main tool for this protection. In this context, this research paper aims to present a vision that leads to an attempt to arrive at an assessment of urban sustainability in development and reconstruction tools in Algeria through a case study of land occupation plan No. 08 in the city of Ain Khadra.. In view of the nature of our research, which is concerned with sustainability and its practices, policies and concepts in the world and at the national level, which by nature contain qualitative and quantitative data, and therefore we will use the integrated (mixed) research method as a method through which to measure. We will use the most famous American system LEED-ND to measure the sustainability of development and development tools, because it contains many mandatory requirements and accreditations. The results of the research will determine the extent to which the latter responds to urban sustainability standards in Algeria, which will help in the future in addressing future urban development.